The effectiveness of bio-anchorage system in reinforcing tropical residual slope - Kuraisha, Kambali; Youventharan, Duraisamy; Rokiah, Othman; Mohd Arif, Sulaiman; Putra Jaya, Ramadhansyah; Siti Noor Linda, Taib (Association of American Publishers, 2025)
Geotechnical phenomena known as “land sliding” encompasses a broad spectrum of ground movements, including rock falls, deep slope failures, and shallow debris flows, particularly in tropical regions. The severity of this issue is higher in regions with a lot of residual soils, like Malaysia, due to the frequent and intense rainfall events and the unique soil properties that make these areas prone to instability. The use of vegetation in soil bioengineering has gained attention recently as an environmentally friendly technique for stabilizing slopes, as most conventional approaches are neither inexpensive nor universally accessible. The primary objective is to understand the bioinspired soil anchoring system’s interaction mechanism to improve the bonding between the residual soil structure in tropical regions. This research is conducted to determine the relationship between the tensile strength of Eugenia Oleina plant roots and the soil parameters of Gambang residual soil. Laboratory testing for soil properties and classification procedures were conducted. Root tensile strength, compressive strength, and shear strength were determined by conducting an unconfined compression test and a direct shear test. These tests are crucial in understanding the mechanical properties of the soil and how it interacts with plant roots under different stress conditions. The comparison between Eugenia Oleina (EO) and Dicranopteris Linearis (DL) plant roots was obtained to recommend the best plant roots for slope stabilization. Out of all the bioinspired soil anchoring systems for tropical slopes, the findings offer the best answer. Thus, it was determined and suggested which plant species would be the most effective tool in residual soil to reinforce tropical slopes.